RANAH PSIKOMOTORIK DALAM KONTEKS PENDIDIKAN : TEKNIK DAN INSTRUMEN ASESMEN YANG EFEKTIF - Nabila Joti Larasati; Sinta Bella; Havifa Nurhijatina; Shaleh (STKIP Subang, 2023)
This article is motivated by the importance of assessment in the psychomotor domain. The psychomotor domain is the domain related to skills or the ability to act after students receive certain learning experiences. The purpose of this research is to find out the Assessment of the Psychomotor Domain, Assessment Techniques and Instruments. The research method used in this research is library research. Data collection techniques by exploring data through literature review, reading, reviewing, and recording data from various sources of relevant articles, journals and books. The data analysis technique used is content analysis. The results of this study provide an understanding of the assessment of the psychomotor domain and the psychomotor assessment instrument technique. Determination of the measuring instrument or assessment instrument to be used is adjusted to the data or measurement results to be obtained, while the accuracy of the assessment instrument in determining the measurement results can be seen from the assessment instrument lattice. The grid contains the material tested, the form of the question, the level of thinking involved, the weight of the question, and the scoring method. The results of measurement and assessment activities then become a consideration for making decisions or conducting evaluations. Keywords: Psychomotor, Assessment, Instrument